2019
DOI: 10.1111/aji.13080
|View full text |Cite
|
Sign up to set email alerts
|

Repeated lipopolysaccharide exposure leads to placental endotoxin tolerance

Abstract: Problem Placental infection induces increased levels of pro‐inflammatory cytokines, which have been implicated in the pathogenesis of pre‐term labor. Endotoxin tolerance is a phenomenon in which exposure to a dose of endotoxin makes tissue less responsive to subsequent exposures. The objective of our study was to determine whether repeated exposure to endotoxin will induce a tolerant phenotype in normal human second‐trimester placental tissue. Methods of study Human second‐trimester placental explants from ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 64 publications
(114 reference statements)
3
9
0
Order By: Relevance
“…47 Immunomodulatory changes in the placenta are accounted for adverse perinatal outcomes such as preterm birth, fetal growth restriction and even fetal death in case of SARS-CoV-2 positive pregnant women admitted for delivery. 6,48,49 Our results are in accordance with previous reports demonstrating that viral infections during pregnancy lead to higher rates of complications in fetuses including spontaneous abortion, premature birth, and intrauterine GUPTA ET AL.…”
Section: Discussionsupporting
confidence: 93%
“…47 Immunomodulatory changes in the placenta are accounted for adverse perinatal outcomes such as preterm birth, fetal growth restriction and even fetal death in case of SARS-CoV-2 positive pregnant women admitted for delivery. 6,48,49 Our results are in accordance with previous reports demonstrating that viral infections during pregnancy lead to higher rates of complications in fetuses including spontaneous abortion, premature birth, and intrauterine GUPTA ET AL.…”
Section: Discussionsupporting
confidence: 93%
“…Our lab demonstrated that endotoxin tolerance exists in placental tissues (109) and we proposed a model of miRNA-mediated placental immune tolerance packaged within EVs. An LPS stimulus primes placental trophoblasts to exhibit a proinflammatory response through the TLR4 pathway, which activates NF-κB to increase pro-inflammatory cytokine expression and release (such as TNFα) (Figure 1).…”
Section: A Placental Model For Microrna-mediated Endotoxin Tolerance mentioning
confidence: 99%
“…Therefore, it is might be possible that postnatal cytokine response does not occur if the dose administered in prenatal period is lower than 200 μg/kg. In a study conducted in humans, induction of second trimester placental tissue with endotoxin has been reported to provide tolerance to repeated ednotoxins (30).…”
Section: Maternal Injection On Day 18th Of Pregnancymentioning
confidence: 99%